Deficiency of the bone mineralization inhibitor NPP1 protects mice against obesity and diabetes - Carmen Huesa; Dongxing Zhu; James D. Glover; Mathieu Ferron; Gerard Karsenty; Elspeth M. Milne; José Luis Millan; S. Faisal Ahmed; Colin Farquharson; Nicholas M. Morton; Vicky E. MacRae (The Company of Biologists, 2014)
The emergence of bone as an endocrine regulator has prompted a re-evaluation of the role of bone mineralization factors in the development of metabolic disease. Ectonucleotide pyrophosphatase/phosphodiesterase-1 (NPP1) controls bone mineralization through the generation of pyrophosphate, and levels of NPP1 are elevated both in dermal fibroblast cultures and muscle of individuals with insulin resistance. We investigated the metabolic phenotype associated with impaired bone metabolism in mice lacking the gene that encodes NPP1 (Enpp1−/− mice). Enpp1−/− mice exhibited mildly improved glucose homeostasis on a normal diet but showed a pronounced resistance to obesity and insulin resistance in response to chronic high-fat feeding. Enpp1−/− mice had increased levels of the insulin-sensitizing bone-derived hormone osteocalcin but unchanged insulin signalling within osteoblasts. A fuller understanding of the pathways of NPP1 could inform the development of novel therapeutic strategies for treating insulin resistance.